I have three log equations about which I'm a bit confused. I need to solve for x.
1) 2 log<sub>5</sub>(x) = 3 log<sub>5</sub>(4)
My work: 2 log<sub>5</sub>(x) - 3 log<sub>5</sub>(4) = 0
The answer is "x = 8".
2) 3 log<sub>2</sub>(x - 1) + log<sub>2</sub>(4) = 5
My work: I tried doing (x-1)^3 and dividing the 3, but it doesn't work out.
The answer is "x = 3".
3) 3<sup>1-2x</sup> = 4<sup>x</sup>
I tried taking the natural log, but I can't get x by itself:
. . .(1 - 2x)ln(3) = xln(4)
Thank you!
__________________________
Edited by stapel -- Reason for edit: formatting
1) 2 log<sub>5</sub>(x) = 3 log<sub>5</sub>(4)
My work: 2 log<sub>5</sub>(x) - 3 log<sub>5</sub>(4) = 0
The answer is "x = 8".
2) 3 log<sub>2</sub>(x - 1) + log<sub>2</sub>(4) = 5
My work: I tried doing (x-1)^3 and dividing the 3, but it doesn't work out.
The answer is "x = 3".
3) 3<sup>1-2x</sup> = 4<sup>x</sup>
I tried taking the natural log, but I can't get x by itself:
. . .(1 - 2x)ln(3) = xln(4)
Thank you!
__________________________
Edited by stapel -- Reason for edit: formatting